Activities and Health Status of Dispatched Public Health Nurses after the Great East Japan Earthquake. Issue 6 (31st July 2014) - Yokoyama, Yoshie; Hirano, Kayoko; Sato, Mari; Abe, Akiko; Uebayashi, Mihoko; Kishi, Emiko; Sato, Mutsuko; Kuroda, Yuuko; Nakaita, Ikumi; Fukushima, Fujio
Abstract Objective This study aimed to elucidate the actual activities conducted by public health nurses during their dispatch and their health status during and after dispatch to the three prefectures most severely affected by the Great East Japan Earthquake. Sample A survey request was sent to a total of 2, 237 facilities. Of these, 778 facilities returned questionnaires from dispatched public health nurses. Results The participants of this study were 1, 570 dispatched health nurses who participated in activities mostly at evacuation centers, followed by evacuees' homes. After dispatch, an earlier postdisaster phase at the start of dispatch was independently associated with poor subjective well‐being, low mood, worsened sleep state, and intense fatigue. Work hours per day were associated with poor subjective well‐being and intense fatigue after dispatch. Conclusion Results suggest that the factor that most strongly affected the postdispatch health of the nurses was the phase that they began their dispatch.